2020
DOI: 10.1111/1440-1681.13446
|View full text |Cite
|
Sign up to set email alerts
|

Cell and extracellular matrix interaction models in benign mesothelial and malignant pleural mesothelioma cells in 2D and 3D in‐vitro

Abstract: Malignant pleural mesothelioma (MPM) is an aggressive tumour that grows in the pleural cavity. MPM spheroids released in the pleural fluid can form new tumour foci. Cell–cell, cell–extracellular matrix (ECM) interactions in 2D and 3D impact malignant cell behaviour during cell adhesion, migration, proliferation and epithelial–mesenchymal transition (EMT). In this study, epithelioid, biphasic and sarcomatoid MPM cell types as well as benign mesothelial cells were tested with regards to the above phenotypes. Fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 46 publications
(50 reference statements)
0
12
1
Order By: Relevance
“…Furthermore, the hydrophobicity of raw carbon nanotubes hampered their dispersion in biological conditions, causing them to clump together in rope-like formations or tangled clumps. These clusters clump together to create discrete multifocal granulomas, which comprise macrophage and fibroblast aggregates [114,115]. Carbon nanotubes were also found in lymph nodes in the mediastinum.…”
Section: Pathogenicity Of Carbon Nanotubesmentioning
confidence: 99%
“…Furthermore, the hydrophobicity of raw carbon nanotubes hampered their dispersion in biological conditions, causing them to clump together in rope-like formations or tangled clumps. These clusters clump together to create discrete multifocal granulomas, which comprise macrophage and fibroblast aggregates [114,115]. Carbon nanotubes were also found in lymph nodes in the mediastinum.…”
Section: Pathogenicity Of Carbon Nanotubesmentioning
confidence: 99%
“…Blum et al ( 27 ) employed WISP, a deconvolution method, to show that different morphological phenotypes in MM correspond to distinct transcriptome phenotypes. More recently, Jargidar et al ( 28 ) tested epithelioid, biphasic and sarcomatoid MM cell types in vitro and found that fibronectin (FN) and homologous cell-derived extracellular matrix (hcd-ECM) treated substratum differentially affected the above phenotypes; 3D MM spheroid invasion was higher in fibronectin-collagen matrices in the epithelioid and biphasic cells, while 3D cell cultures of epithelioid and sarcomatoid MM cells in fibronectin-collagen showed a higher contractility compared to hcd-ECM-collagen. Collectively, these results support our findings that histological subtypes are remarkably consistent with the MM-derived epithelioid-like, biphasic-like, and sarcomatoid-like tumor cell populations.…”
Section: Discussionmentioning
confidence: 97%
“…Also, cell-ECM interactions have been generally recognized as an important mechanism for tumor cell proliferation, migration and invasion. 36 Thus, the components (including fibronectin, thrombospondin and chondroitin sulfate proteoglycans) of the ECM and related genes may be crucial targets for the development and progression of cancers, including MPM. 37 This hypothesis had been demonstrated by previous studies.…”
Section: Discussionmentioning
confidence: 99%